Index Coded PSK Modulation in Vehicle to Vehicle Communication - Pachat, Jesy; Karat, Nujoom Sageer; Mahesh, Anjana A.; P, Deepthi P.; Rajan, B. Sundar (IEEE Vehicular Technology Conference, 2021)
Vehicle to vehicle (V2V) communication has gained its importance in recent years. In this work we consider the index coding problem (ICP) over noisy channel in V2V communication phase of message dissemination. The ICP in V2V communication is considered as device to device ICP with transmitting nodes as receiving nodes also. The index code is used in noisy scenario over AWGN channel and the broadcast vectors are mapped to suitable M-PSK signal constellations to save bandwidth, thus increasing the bandwidth efficiency. An algorithm is proposed to derive suitable mapping of the broadcast vectors to M-PSK signal constellation for improving the error performance. Performance improvement in terms of PSK index coding gain is discussed. While one vehicle transmits, the proposed algorithm provides performance improvement for at least one of the remaining vehicles, in most of the scenarios, while not penalizing the other vehicles.